Penerapan media whiteboard.chat dalam penulisan teks deskripsi berbahasa jawa pada siswa kelas VII SMP N 2 Warureja semester genap tahun 2022/2023 - Ramadani, Desta Putri; Sunarya, Sunarya; Werdiningsih, Yuli Kurniati (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2023)
This research aims to make students more excited, namely by providing strategies or ways that can attract the attention of students. Therefore, efforts to improve skills in presenting material are needed to attract the attention of students. Media that can be used in learning to write Javanese description texts is Whiteboard.Chat media. It is expected that with Whiteboard.Chat media students will be able to describe Javanese description text.In this study, data analysis was carried out by describing or explaining the results of data obtained from the application of whiteboard.chat media in writing Javanese description texts for grade VII students of SMP N 2 Warureja in the even semester of 2022/2023. The results of the data obtained based on test techniques and non-test techniques are explained using the descriptive qualitative approach method. From the research that has been carried out, a percentage of knowledge aspects that state good results are obtained. Thus students can more easily understand the text description of the Endel Mask dance because students are directly involved in learning. The results of this study on the knowledge aspect of 30 students can already use whiteboard.chat media and write text descriptions about the Endel Mask dance. At an average score of 80 in the good category there were 15 learners. In an average score of 90 there were 7 students and got a score of 100 there were 8 students, none of the students scored below the KKM score. From the data on learning outcomes of skill aspects by applying whiteboard media. Chat obtained an average rating of 80.